The Effect of Job Satisfaction on Turnover Intention through Person-Organization Fit at PT PLN (Persero) UP3 Tanjung Karang - Hajarroh Putri, Ajengriska; Permatasari, Berlintina (Universitas Pamulang, 2024)
This study aims to test and analyze the effect of Job Satisfaction on Turnover Intention through Person Organization Fit as a moderating variable on employees of PT PLN (Persero) UP3 Tanjung Karang. The population in this study were employees of PT PLN (Persero) UP3 Tanjung Karang totaling 65 people. The sample used in this study was using the non-probability sampling technique chosen was saturated sampling, which is a sampling method if all members of the population are used as samples. This study is a descriptive study with a quantitative approach. In this study, data were collected using a questionnaire of 65 respondents. Data analysis used simple linear regression analysis and Moderated Regression Analysis (MRA). The results of the simple linear regression analysis showed that Job Satisfaction partially had a negative and significant effect on Turnover Intention. While Moderated Regression Analysis (MRA) showed that Person Organization Fit was unable to moderate the relationship between Job Satisfaction and Turnover Intention.